2011
DOI: 10.2174/187152911795945150
|View full text |Cite
|
Sign up to set email alerts
|

Is It Possible to Apply Secondary Stroke Prevention Guidelines to Very Old Populations?

Abstract: The aging population is an undeniable reality which must be faced by all health systems all over the world. Among people over 80 years old, increase in stroke incidence, high mortality rates and adverse outcomes are problems of major public concern. Lack of evidence-based data to guide rational decision making on vascular risk factors management to avoid recurrence in elderly stroke patients increases the areas of uncertainty, and sometimes favors medical inertia at the time of taking care of this growing elde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although they are at greatest risk of stroke, data from several studies suggests that BP is less well controlled in older adults . Undertreatment may be related to concerns about side effects or interactions, both of which may be more common in older than younger adults …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although they are at greatest risk of stroke, data from several studies suggests that BP is less well controlled in older adults . Undertreatment may be related to concerns about side effects or interactions, both of which may be more common in older than younger adults …”
mentioning
confidence: 99%
“…[7][8][9] Undertreatment may be related to concerns about side effects or interactions, both of which may be more common in older than younger adults. 10,11 Several trials have demonstrated that hypertension treatment in older adults can be undertaken with minimal risk. [12][13][14][15] Furthermore, the Hypertension in the Very Elderly Trial (HYVET) showed a 30% reduction in stroke (P = .06) and 21% reduction in mortality (P = .02) with BP lowering.…”
mentioning
confidence: 99%
“…Antihypertensive medications have been regularly used to reduce BP; however, low adherence to antihypertensive medications is prevalent due to various factors including prior experience of medication side effects [ 10 ], leading to poor BP control [ 11 ]. Uncontrolled BP maybe related to side effects or interactions of antihypertensives and this observation is more commonly noted in older populations [ 12 , 13 ]. Moreover, a former meta-analysis has shown that only angiotensin-converting enzyme inhibition (ACEI) plus diuretics significantly decreases recurrent stroke events, and no significant association between BP reduction and all adverse outcomes was found [ 14 ].…”
Section: Introductionmentioning
confidence: 99%